The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fendo.2022.858012
|View full text |Cite
|
Sign up to set email alerts
|

A Hypothesis From Metabolomics Analysis of Diabetic Retinopathy: Arginine-Creatine Metabolic Pathway May Be a New Treatment Strategy for Diabetic Retinopathy

Abstract: Diabetic retinopathy is one of the serious complications of diabetes, which the leading causes of blindness worldwide, and its irreversibility renders the existing treatment methods unsatisfactory. Early detection and timely intervention can effectively reduce the damage caused by diabetic retinopathy. Metabolomics is a branch of systems biology and a powerful tool for studying pathophysiological processes, which can help identify the characteristic metabolic changes marking the progression of diabetic retinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 133 publications
0
7
0
Order By: Relevance
“…Therefore, the identification of biomarkers associated with disease progression can be very helpful. 20 Metabolomics is a branch of systems biology and a powerful tool for studying pathophysiological processes, which can aid in identifying the characteristic metabolic changes indicative of DR progression. 21 Therefore, this study intended to analyze and identify serum metabolites and Sema3A levels in DR patients, that could be useful biomarkers of DR progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the identification of biomarkers associated with disease progression can be very helpful. 20 Metabolomics is a branch of systems biology and a powerful tool for studying pathophysiological processes, which can aid in identifying the characteristic metabolic changes indicative of DR progression. 21 Therefore, this study intended to analyze and identify serum metabolites and Sema3A levels in DR patients, that could be useful biomarkers of DR progression.…”
Section: Discussionmentioning
confidence: 99%
“…For completing the cycle, ornithine is then transformed back to arginine. Alternatively, ornithine through the intermediate glutamic γ-semialdehyde may be metabolized to proline 20,34 . Our findings add to the growing body of evidence that alterations in urea cycle metabolites, especially arginine and citrulline, are associated with DR. Arginine also acts as a substrate for the enzyme NOS, which catalyzes a process that results in citrulline and NO; a vasodilator that is essential for maintaining the health of the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…In oxygen-induced retinopathy (OIR) mouse model, oral administration of creatine suppressed neovascularization. Several studies revealed the therapeutic potential of creatine supplementation on DR, as well as preventive approaches [ 72 ].…”
Section: Application Of Metabolomics In Ocular Diseasesmentioning
confidence: 99%
“…Second, some of these potential biomarkers have preventive potentials. Some metabolites were identified as protective metabolites for DR by in vitro and in vivo study, such as PGF2α and creatine [ 27 , 72 ]. In fact, most studies only revealed disturbed metabolites in diseases and do not further explore the preventive effects in secondary care.…”
Section: Conclusion and Expert Recommendations In The Context Of 3p M...mentioning
confidence: 99%
“…Similarly, surgical intervention, while effective for some complex cases of diabetic retinopathy, carries high risks and recurrence rates. [5–7] Despite significant advancements in medical technology improving visual acuity and quality of life for DR patients posttreatment, the risk of complications such as poor blood sugar control, fundus hemorrhage, and elevated intraocular pressure remains due to a lack of self-care and medication knowledge post-discharge. Therefore, providing effective extended care is crucial to enhance home care effectiveness and improve treatment and rehabilitation levels.…”
Section: Introductionmentioning
confidence: 99%